2018
DOI: 10.3390/e20120937
|View full text |Cite
|
Sign up to set email alerts
|

Additive Manufacturing of High-Entropy Alloys: A Review

Abstract: Owing to the reduced defects, low cost, and high efficiency, the additive manufacturing (AM) technique has attracted increasingly attention and has been applied in high-entropy alloys (HEAs) in recent years. It was found that AM-processed HEAs possess an optimized microstructure and improved mechanical properties. However, no report has been proposed to review the application of the AM method in preparing bulk HEAs. Hence, it is necessary to introduce AM-processed HEAs in terms of applications, microstructures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 179 publications
(59 citation statements)
references
References 76 publications
0
59
0
Order By: Relevance
“…Whereas a great deal of work is currently underway on additive manufacturing of these three conventional alloy classes, three-dimensional (3D) printing of 3d TM HEAs/ CCAs has received much less attention. [8][9][10][11][12][13][14][15][16][17][18] In this paper, we explore the microstructure and tensile properties of Al 0.3 CoCrFeNi HEA processed by powder-bed selective laser melting (SLM). Our alloy selection is motivated by the exceptional tunability principle of this FCC-based HEA, which has been demonstrated for wrought products; i.e., multiphase FCC-L1 2 , FCC-B2 or FCC-B2-r microstructures can be generated by tuning the cold rolling percentage and annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas a great deal of work is currently underway on additive manufacturing of these three conventional alloy classes, three-dimensional (3D) printing of 3d TM HEAs/ CCAs has received much less attention. [8][9][10][11][12][13][14][15][16][17][18] In this paper, we explore the microstructure and tensile properties of Al 0.3 CoCrFeNi HEA processed by powder-bed selective laser melting (SLM). Our alloy selection is motivated by the exceptional tunability principle of this FCC-based HEA, which has been demonstrated for wrought products; i.e., multiphase FCC-L1 2 , FCC-B2 or FCC-B2-r microstructures can be generated by tuning the cold rolling percentage and annealing temperature.…”
Section: Introductionmentioning
confidence: 99%
“…It connects capillarity phenomena and entropy changes in the considered phase transition. Having in mind the outstanding rule of the entropy concepts in different related problems [35][36][37][38][39][40][41], such an approach can be considered already in advance as highly prospective. An extension of our method to ice-crystal nucleation in water will be presented in an accompanying paper [42].…”
Section: Introductionmentioning
confidence: 99%
“…Pham et al reported extraordinary high yield strength of 520 MPa and elongation of ~60% in PBF AM SS 316 L (double of annealed commercial SS 316 L alloys) and highlighted fine subgrains having high dislocation density and strong twinning-induced plasticity 28 . Recently AM reaches HEAs, for example, AM CrCoNiFe (Al, Ti, Mn) [31][32][33] and AM refractory HEAs (MoNbTaW, TiZrNbTa) 34,35 . Noticeably, Li et al showed tensile strength over 600 MPa in a high energy laser AM CrCoNiFeMn HEA (not less than cast-wrought CrCoNiFeMn HEA) having a large number of dislocation pile-ups and nanotwins in refined grains 33 .…”
mentioning
confidence: 99%